Development and validation of a Chinese version of a questionnaire to evaluate the knowledge, attitude, and practice about breast cancer screening among financial female workers in Taiwan - Lin, Jia-Yi; Hung, Ching-I; Li, Tsai-Chung; Chang, Ta-Yuan (Frontiers in Oncology, 2025)
IntroductionThis study aimed to develop a Chinese version of a questionnaire to assess the knowledge, attitude, and practice of breast cancer screening among female workers in the financial industry and to evaluate its reliability and validity.MethodsAn item pool relevant to knowledge of and attitudes toward breast cancer screening was generated, and 16 experts assessed the validity of the instrument’s content relevance and domain coverage. We conducted a cross-sectional study of 1,511 women working in the financial industry in Taiwan. The questionnaire’s construct validity was assessed using correlations between the items and other scales to evaluate knowledge of and attitudes toward breast cancer screening. The internal consistency was evaluated using Cronbach’s α values.ResultsPositive and negative attitudes toward mammography and attitudes toward reasons for not receiving a mammography accounted for 68.3%, 10.3%, and 20.9% of total variance, respectively. The Cronbach’s α coefficients for knowledge of and attitudes toward breast cancer screening were 0.37 and 0.91, respectively. One interquartile range (IQR) increase in the total scores on the breast cancer attitudes toward mammography (6 points; adjusted odds ratio [AOR]: 1.47, 95% confidence interval [CI]: 1.24-1.75) and the total scores on the reasons for not receiving a mammography (8 points; AOR: 1.79; 95% CI: 1.46-2.20) were significantly associated with the practice of having ever received a mammography. Both scores showed significant exposure-response associations.ConclusionOur findings indicate that the Chinese version of the questionnaire used to evaluate attitudes and practices toward breast cancer screening among female workers in the financial industry demonstrated good construct validity and internal consistency.